Speaking Skill Between Screen and Classroom: The Experiences of Teachers and Students in Middle Schools - Bal, Mazhar; Okur, Muhammed Davut (Psychology in the schools, 2025)
ABSTRACT This study aims to examine the perspectives of middle school students and Turkish teachers regarding the development of speaking skills through face‐to‐face and distance education. Thirty‐two Turkish language teachers and 96 middle school students participated in the study, which employed a case study design, a qualitative research method. Data were collected through a semi‐structured interview form and analyzed using content analysis. The findings indicated that both teachers and students perceived face‐to‐face instruction as more effective. Teachers favored face‐to‐face education due to the advantages of utilizing body language, providing immediate feedback, and employing diverse methodologies, while they considered distance education as a viable alternative for use in exigent circumstances. Although students also expressed a preference for face‐to‐face education, they demonstrated a more positive attitude towards distance education compared to teachers. The perception of distance education varied according to grade level. Lower grades exhibited a mask and distance‐oriented approach, whereas upper grades focused on the communication environment. Notably, eighth‐grade students demonstrated greater awareness of the flexibility and accessibility advantages of distance education. A significant finding revealed that some students experienced reduced anxiety in distance education. This suggests that distance education may serve as a supportive tool in developing speaking skills. However, inadequacies in technical infrastructure and communication gaps impede the effective utilization of this potential. Summary While educators demonstrate a preference for in‐person instruction, students exhibit a more favorable disposition towards distance education, suggesting the potential efficacy of a blended learning model. Students experiencing high levels of speaking anxiety report increased comfort in distance education environments, indicating that this modality may serve as a supportive tool. As students progress through higher grade levels, they demonstrate increased awareness of the advantages of flexibility and accessibility inherent in distance education. The limited implementation of speaking strategies by educators in distance education contexts highlights the necessity for professional development in this domain. Inadequacies in technological infrastructure and disruptions in communication impede the full realization of distance education's potential.